Ethics in Public Health and Health Policy
VIII, 229 p.
Keywords: Ethical issues within public health and health policy, related e.g. to pandemic plans and vaccination policies (c.f. SARS or the New Influenza), preventive measures like screening (e.g. for breast cancer or dementia) or health information campaigns, social inequalities or health care rationing gain increasing relevance around the world. Evidence-based information for a valid benefit-harm assessment is often rare and hard to get for participants in public health interventions. Program implementations often disregard requirements of a fair decision-making process (like public participation, transparency, etc.). Originating from an international conference (based on a call for abstracts and external review), this volume contains contributions from a group of experienced scholars from multiple disciplines and countries, covering (i) conceptual foundations of public health ethics, (ii) methodological approaches and (iii) normative analyses of specific issues and cases. In bridging theoretical foundations with practical applications, the volume shall provide a valuable resource for researchers, practitioners and students in the field. .